2022
DOI: 10.1038/s41598-022-22380-0
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity and genomic characterization of the biocontrol agent Bacillus velezensis CMRP 4489

Abstract: The development of bio-based products has increased in recent years, and species of the Bacillus genus have been widely used for product development due to their elevated production of antimicrobial molecules and resistance to extreme environmental conditions through endospore formation. In this context, the antifungal potential of Bacillus velezensis CMRP 4489 was investigated using in silico predictions of secondary metabolites in its genome and in vitro tests against the following phytopathogenic fungi: Scl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…There are some studies on the effect of biocontrol strain on pathogens, such as the ability of B. subtilis Y2 to inhibit the growth of Alternaria brassicicola in pear fruit [41]. The antagonistic activity of B. velezensis CMRP 4489 could inhibit the growth of pathogens by the formation of biofilm [42].…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies on the effect of biocontrol strain on pathogens, such as the ability of B. subtilis Y2 to inhibit the growth of Alternaria brassicicola in pear fruit [41]. The antagonistic activity of B. velezensis CMRP 4489 could inhibit the growth of pathogens by the formation of biofilm [42].…”
Section: Discussionmentioning
confidence: 99%
“…Auxin is an important factor in phosphorus regulation [160]. PSB can also help Solanaceae resist pathogens after being soaked in bacterial fertilizers, such as reducing Fusarium oxysporum [161], Aspergillus, Penicillium [162], and Botrytis cinerea by 48% [163], as well as Macropomina phaseolina [164] and Pseudomonas aeruginosa [165], and this may be related to the discovery of antibiotic-resistance genes in PSB [166]. Studies have shown that under lowphosphorus stress, bacteria are more sensitive to phosphorus enrichment and recruitment than fungi [167].…”
Section: Colonization Of Bacterial Communities In Plants Is Influence...mentioning
confidence: 99%
“…The complete genome was then deposited in DDBJ / EMBL / GenBank under the accession number CP023748 (Baptista et al, 2018). Additionally, LABIM40 was deposited as strain CMRP 4489 in the Coleções Microbiológicas da Rede Paranaense (CMRP) network at the Federal University of Paraná, in Curitiba, Brazil (Baptista et al, 2022). Prior to each experiment, the LABIM40 strain was activated from the cryopreserved stock culture on nutrient agar (NA) plates and incubated at 30 °C with a 12 hour photoperiod until colony formation occurred.…”
Section: Isolation and Identification Of B Velezensis Labim40 Strainmentioning
confidence: 99%